Analysis of Factors Affecting Integrated Public Service Performance - Hanifah, Humairoh Hudiyatul (Efficient: Indonesian Journal of Development Economics, 2019)
The purpose of this study is to analyze the influence of competence, motivation, and work environment of employees on the performance of public service Department of Investment and One Stop Service (DPM-PTSP) Semarang City. The research method used in this research is quantitative research method with sampling technique Quota Sampling and Judgment Sampling. Processing techniques and data analysis used are test validity, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis test. The result of the research shows that employee competency, employee motivation, and work environment have positive and significant influence on the performance of public service at One Stop Service and One Stop Service (DPM-PTSP) Semarang City based on the indicators that have been determined in the research. However, there are still some unsuitable indicators, such as employees who need time to adapt to the latest rules, policies, technologies and systems, the need for additional facilities, simplification of licensing compliance requirements and submission process, provision of information on changes in the requirements of the completeness of the licenses and the submission process through the official web of the One Stop Service and One Stop Service (DPM-PTSP) of Semarang City or attached to the licensing application form. Tujuan penelitian ini adalah menganalisis pengaruh kompetensi, motivasi, dan lingkungan kerja pegawai terhadap kinerja pelayanan publik Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPM-PTSP) Kota Semarang. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kuantitatif dengan teknik pengambilan sampel Quota Sampling dan Judgement Sampling. Teknik pengolahan dan analisis data yang digunakan adalah uji validitas, uji reliabilitas, uji asumsi klasik, analisis regresi linier berganda, dan uji hipotesis. Hasil penelitian menunjukkan kompetensi pegawai, motivasi pegawai, dan lingkungan kerja pegawai memiliki pengaruh yang positif dan signifikan terhadap kinerja pelayanan publik di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPM-PTSP) Kota Semarang berdasarkan indikator-indikator yang telah ditetapkan dalam penelitian. Namun masih ada beberapa indikator yang belum sesuai, seperti pegawai yang membutuhkan waktu untuk menyesuaikan diri dengan aturan, kebijakan, teknologi, dan sistem terbaru, lalu perlunya penambahan fasilitas, penyederhanaan persyaratan kelengkapan perizinan dan proses pengajuan, pemberian informasi perubahan persyaratan kelengkapan perizinan dan proses pengajuan melalui web resmi Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPM-PTSP) Kota Semarang atau terlampir pada form pengajuan perizinan.